Axial compressive behavior and load-bearing capacity of steel tubular-corrugated steel plate confined concrete composite columns. (October 2022) - Sun, Ze-Xuan; Zou, Yun; Wang, Cheng-Quan; Pan, Jie; Wang, Li; Chen, Ming
Abstract: A novel type of steel tubular-corrugated steel plate confined concrete composite column (S-CSCPC column) is proposed in this paper. In order to evaluate the axial compressive behavior of the new composite column, a total of 11 S-CSCPC columns are designed and tested, and the corresponding failure modes and load–strain curves are observed. By analyzing the strain and stress of corrugated steel plate, the confinement mechanism of core concrete is discussed. It's found that the corrugated steel plate bears little vertical stress, while its main function is to provide transverse confining stress for the core concrete. And different positions of corrugated steel plate have different confinement effect on the core concrete. As well, the influence of material properties and section sizes of S-CSCPC column on the bearing capacity and the effective confining stress ( f r ) of core concrete is explored through FE simulation and parameter analysis. Moreover, based on the superposition principle and the compressive strength calculation method of confined concrete proposed by Mander which considers the effective confining stress, a formula for calculating the bearing capacity of S-CSCPC column is proposed, whose results predict reasonably with the experimental and numerical results.